Älgexplosionen på 70- och 80-talet, ett hot mot sågverket? - Kvarnström, Per (SLU/School for Forest Management, 2010)
The background of this study is an article in the hunting magazine “Svensk Jakt” where Karl Hedin claims that his sawmills has not noticed any significant moose damages in the timber. The purpose with the study is to find out the causes to the moose explosion and what it has led to in today’s forests. A questionnaire has been sent out to sawmills in the region Dalarna with the purpose of finding out if sawmills receive moose-damaged timber and what they think about how they foresee future development. There were two causes of the moose explosion, that had effects on the moose population. The first cause was that the moose hunters wanted to raise the moose population, and by raising the calf shooting and by saving the cows they succeeded. The second cause was changing methods in Swedish forestry. Extensive clear-cuttings led to much more food for the moose and the population grew. The moose ravages in the forests have a large negative effect on the forest. The growth in the stands decline and the number of stems per hectar drop significantly. The moose grazing on pines leads to different types of damages, trunk break, treetop grazing and bark eating. These damages on the pine leads to technical damages which leads to that the price on the log drops. The questionnaire shows that four of five sawmills has not noticed the moose explosion. The fifth sawmill writes that they don’t know. Three out of seven sawmills doesn’t see the moose as a threat. On the question of what they think about the future seven people answered. Four people believed that we can handle the problem in a good way and that business will continue in the same way as it has been. There were other interesting things that appeared in answers to the questionnaire, several sawmills will handle the problem with moose-damaged timber by installing an x-ray equipment. The majority of the people that answered believes that we can prevent a new moose explosion by a proper management of the moose population.